Disproportionation of ethylbenzene in the presence of C-8 aromatics - Sharnappa, N.; Pai, S.; Bokade, Vijay V. (Journal of Natural Gas Chemistry, 2009)
The selective synthesis of p-diethylbenzene (p-DEB) by disproportionation of ethylbenzene (EB) in the presence of aromatics like m- and p-xylene isomers has been studied over a pore size regulated HZSM-5 catalyst. The industrial feed having different compositions of ethylbenzene and xylene isomers was used for the experimentation. Hence, they were expected to hinder the movement of reactant molecules both on the external surface and within the zeolite channels. It was observed that irrespective of the different feed compositions the concentration of the xylene isomers was intact in the product. There is no other byproducts formation like para-ethylmethyl benzene. The effects of varying the concentration of aromatic compounds in the feed on ethylbenzene conversion and product distribution over the parent and modified H-ZSM-5 catalyst have been discussed. Ethylbenzene disproportionation reaction follows the pseudo first order reaction with an activation energy of 8.6 kcal/mol.
Keywords: Catalyst; diethylbenzene; disproportionation; ethylbenzene; xylene isomers